2017
DOI: 10.4064/cm6184-12-2015
|View full text |Cite
|
Sign up to set email alerts
|

Some isomorphic properties in $K(X,Y)$ and in projective tensor products

Abstract: We study the (DPrcp) and the Gelfand Phillips property in the space of compact operators. Moreover we give some sufficient conditions in order that a projective tensor product of two Banach spaces is sequentially Right (SR) or it has the L-limited property. Moreover we study the Bourgain Diestel property (BD), the (RDP *) property in the space K w * (X, Y). We introduce the dual (SR *) property and we give a characterization of it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Our aim in this section is to obtain some suitable conditions on X and Y such that any dominated operator T from C(Ω, X) into Y is p-convergent. Recall that, the authors in [9,19] by using Right topology, independently, proved that a sequence (x n ) n in a Banach space X is Right null if and only if it is Dunford-Pettis and weakly null. Also, they showed that a sequence (x n ) n in a Banach space X is Right Cauchy if and only if it is Dunford-Pettis and weakly Cauchy.…”
Section: Dunford-pettis Relatively Compact Property Of Order Pmentioning
confidence: 99%
“…Our aim in this section is to obtain some suitable conditions on X and Y such that any dominated operator T from C(Ω, X) into Y is p-convergent. Recall that, the authors in [9,19] by using Right topology, independently, proved that a sequence (x n ) n in a Banach space X is Right null if and only if it is Dunford-Pettis and weakly null. Also, they showed that a sequence (x n ) n in a Banach space X is Right Cauchy if and only if it is Dunford-Pettis and weakly Cauchy.…”
Section: Dunford-pettis Relatively Compact Property Of Order Pmentioning
confidence: 99%
“…Later on Kacena [21], by introducing the notion of Right set in the dual of X, gave a characterization of those Banach spaces which have the sequentially Right property. Recently, Cilia and Emmanuele [8] and Ghenciu [18], obtained some sufficient conditions implying that the projective tensor product of two Banach spaces has the sequentially Right property. Moreover, they introduced the concept sequentially Right * property on Banach spaces and gave its characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they introduced the concept sequentially Right * property on Banach spaces and gave its characterization. For more information and examples of those spaces with the sequentially Right property and sequentially Right * property, we refer to [8,17,21,26]. Recently, Ghenciu [19], by introducing the concepts of Dunford-Pettis p-convergent operators, p-Right sets and p-sequentially Right property obtained some characterizations of these notions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Banach space X has the (L)-Dunford-Pettis property, if every (L)-Dunford-Pettis subset of X * is relatively weakly compact. Recently, Cilia and Emmanuele in [8] and Ghenciu in [22] obtained a characterization for Right null sequences. In fact, they showed that a sequence (x n ) n in a Banach space X is Right null if and only if it is Dunford-Pettis and weakly null.…”
Section: Introductionmentioning
confidence: 99%